Advancing the thermal stability of 3D ICs using logi-thermal simulation. Issue 12 (December 2015) - Nagy, Gergely; Horváth, Péter; Pohl, László; Poppe, András
Abstract: 3D ICs have emerged in the past few years. While they solve a large number of problems related to scaling, they also create new ones. Removing the heat from the layers far from the cooling facilities is a great challenge still under intensive research. This paper shows how logi-thermal simulation can be used to predict the operation parameters of large digital systems realized in 3D ICs. The method can be effectively used to guide place-and-route algorithms and to find the thermal bottlenecks.